THE EFFECT OF FAMILY COUNSELING SERVICES ON THE RELATIONSHIP BETWEEN PARENTS AND PROBLEMATIC ELEMENTARY SCHOOL STUDENTS - Sisilia Prima Yanuaria Buka; Rashid Rahman; Faisal Razak; Arif Muzayin Shofwan (Yayasan Adra Karima Hubbi, 2025)
Family dynamics play a crucial role in shaping children's behavior and academic success. Conflicts between parents and children can disrupt these dynamics, particularly for elementary school students with behavioral challenges. This study examines the effect of family counseling services on improving the relationship between parents and problematic elementary school students. The research aims to evaluate whether structured family counseling can enhance communication, mutual understanding, and collaboration between parents and their children. A quasi-experimental research design was employed, utilizing pre-test and post-test measures with a control group. The sample consisted of 50 families selected through purposive sampling, divided equally into experimental and control groups. Data were collected using relationship quality questionnaires, observational records, and structured interviews. The results indicate a significant improvement in the parent-child relationship within the experimental group compared to the control group. Participants reported enhanced communication, reduced conflict, and increased emotional bonding after engaging in the family counseling sessions. These findings suggest that family counseling is an effective intervention for addressing relational issues and fostering a supportive environment for elementary school students with behavioral difficulties.